2015
DOI: 10.1007/s00246-015-1225-2
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Dynamic NT-proBNP and hs-cTnT Response to Exercise Challenge in Asymptomatic Children with Moderate Aortic Valve Regurgitation or Moderate Aortic Valve Stenosis

Abstract: Patients with congenital aortic valve stenosis (AVS) can remain asymptomatic but may develop progressive and often underestimated exercise intolerance. The risk of increased left ventricular (LV) wall stress, irreversible myocardial fibrosis and sudden death in untreated patients warrants earlier intervention. The timing for curative therapy for severe AVS is clear, but optimal timing for moderate stenosis (modAS) is unknown. AVS often coexists with aortic regurgitation, which adds a volume overload to an alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The resting blood samples were taken after 20-30 minutes after supine rest and the post exercise sample was taken 2-3 minutes after the cessation of exercise. There were only three studies where blood samples were taken at serial intervals post exercise (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…The resting blood samples were taken after 20-30 minutes after supine rest and the post exercise sample was taken 2-3 minutes after the cessation of exercise. There were only three studies where blood samples were taken at serial intervals post exercise (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Highly sensitive troponin, however, was significantly higher at rest in both disease groups and the levels remained similar at 20 and 40 minutes into recovery. 14 The results suggest a novel way to assess valvular heart disease.…”
Section: Discussionmentioning
confidence: 96%
“…The increase in hs-cTnT was significant only at 60 minutes into recovery for moderate AS and AR. 14 The study looking at CT-ADP and HMWM during exercise showed that these levels did not change significantly between rest and exercise (P = .45 and P = .65, respectively). In 4 out of the 10 subjects, no valid aortic valve velocity could be recorded on exercise; however, in the remaining six patients, CT-ADP during exercise correlated well with aortic valve peak velocity (rho 0.82, P = .04).…”
Section: Serial Biomarker Measurementsmentioning
confidence: 90%
See 2 more Smart Citations